2015
DOI: 10.1086/683252
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evolution under Fluctuating Thermal Conditions Does Not Reproduce Patterns of Adaptive Clinal Differentiation inDrosophila melanogaster

Abstract: Experimental evolution can be a useful tool for testing the impact of environmental factors on adaptive changes in populations, and this approach is being increasingly used to understand the potential for evolutionary responses in populations under changing climates. However, selective factors will often be more complex in natural populations than in laboratory environments and produce different patterns of adaptive differentiation. Here we test the ability of laboratory experimental evolution under different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 60 publications
2
45
0
Order By: Relevance
“…; Kellermann et al. ). Hence, given the moderate size of available inbred isofemale line collections and the considerable effort and time to establish them, we anticipate that freshly collected isofemale lines will continue to be used to seed E&R studies.…”
Section: Discussionmentioning
confidence: 98%
“…; Kellermann et al. ). Hence, given the moderate size of available inbred isofemale line collections and the considerable effort and time to establish them, we anticipate that freshly collected isofemale lines will continue to be used to seed E&R studies.…”
Section: Discussionmentioning
confidence: 98%
“…However, subsequent field manipulations are necessary to confirm reputed agents of local adaptation (Agrawal ), as laboratory and greenhouse environments can be poor proxies for natural conditions (Kellermann et al . ; Poorter et al . ).…”
Section: Question 2: How Do Agents Of Selection Interact To Generate mentioning
confidence: 99%
“…An increasing number of evolutionary and ecological studies have recently focused on the effects of short-or long-term variation of temperatures (Ketola et al, 2004;Kingsolver et al, 2009;Hallsson and Bjorklund, 2012;Kellermann et al, 2015). Using fluctuating temperatures can be argued to have a greater ecological relevance compared with constant ones, as they are a better proxy of a natural environment (Boyce et al, 2006;Schreiber, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term adaptive responses to varying temperatures are expected to depend on the ability to rapidly adjust the phenotype by phenotypic plasticity (Pal, 1998;Lande, 2009;Chevin and Lande, 2010;Kellermann et al, 2015). For instance, Manenti et al (2014) found high levels of plasticity in a natural population of Drosophila simulans induced by different fluctuating thermal regimes that differed in the amplitude and predictability of daily fluctuations.…”
Section: Introductionmentioning
confidence: 99%